A STUDY OF POVERTY AND INEQUALITY: A CRITICAL EXAMINATION OF ISSUES, CONCEPTS AND MEASUREMENTS - A LITERATURE VIEWS - C., Vasudevan (International Journal of Research -GRANTHAALAYAH, 2019)
Alleviation of Poverty is a crucial issue in the economic policy of most of the developing countries. But the Understanding of poverty and inequality needs a different aptitude of approaching its issues, concepts and measurement. Accordingly, this article examining the study of nature of issues, concepts and measurements of poverty and inequality which are closely associated with different multivariate phenomenon and magnitudes. This study also emphasized that the poverty and inequality must be approached in a broader view rather than a narrowed one.